PENCIPTAAN DESAIN BUSANA ANDROGINI SEBAGAI INOVASI INDUSTRI BATIK MASARAN SRAGEN - Handayani, Endang Sri; Munir, M Fachrul; Choiri, Rhochimatul (Institut Seni Indoensia Surakarta, 2022)
Creating androgyny fashion is one of innovation to developt industry of Batik Masaran. The high of market demand that already bored with the monoton patern shirt made the researcher want to make new androgyny fashion design that combinated with Batik Masaran. The innovation of androgyny style can be apply on any gender and any situation. Creating androgyny fashion design is using theory of art creation by Gustami that include three methods, there are exploration, design, and implementation. On the exploration step, the researcher made an idea research in many source, and then on design step there is procces for looking best design that will materialization as artwork. On the implementation step, there is few step including making illustration mode, making fashion pattern, cutting the fabric, and sewing.